Clinical values of metagenomic next-generation sequencing in patients with severe pneumonia: a systematic review and meta-analysis - Lv, Minjie; Zhu, Changjun; Zhu, Chenghua; Yao, Jing; Xie, Lixu; Zhang, Changwen; Huang, Jianling; Du, Xingran; Feng, Ganzhu (Frontiers in Cellular and Infection Microbiology, 2023)
Background Clinical values of metagenomic next-generation sequencing (mNGS) in patients with severe pneumonia remain controversial. Therefore, we conduct this meta-analysis to evaluate the diagnostic performance of mNGS for pathogen detection and its role in the prognosis of severe pneumonia. Methods We systematically searched the literature published in PubMed, Embase, Cochrane Library, Web of Science, Clinical Trials.gov, CNKI, Wanfang Data, and CBM from the inception to the 28th September 2022. Relevant trials comparing mNGS with conventional methods applied to patients with severe pneumonia were included. The primary outcomes of this study were the pathogen-positive rate, the 28-day mortality, and the 90-day mortality; secondary outcomes included the duration of mechanical ventilation, the length of hospital stay, and the length of stay in the ICU. Results Totally, 24 publications with 3220 patients met the inclusion criteria and were enrolled in this study. Compared with conventional methods (45.78%, 705/1540), mNGS (80.48%, 1233/1532) significantly increased the positive rate of pathogen detection [OR = 6.81, 95% CI (4.59, 10.11, P < 0.001]. The pooled 28-day and 90-day mortality in mNGS group were 15.08% (38/252) and 22.36% (36/161), respectively, which were significantly lower than those in conventional methods group 33.05% (117/354) [OR = 0.35, 95% CI (0.23, 0.55), P < 0.001, I2 = 0%] and 43.43%(109/251) [OR = 0.34, 95% CI (0.21, 0.54), P < 0.001]. Meanwhile, adjusted treatment based on the results of mNGS shortened the length of hospital stay [MD = -2.76, 95% CI (− 3.56, − 1.96), P < 0.001] and the length of stay in ICU [MD = -4.11, 95% CI (− 5.35, − 2.87), P < 0.001]. Conclusions The pathogen detection positive rate of mNGS was much higher than that of conventional methods. Adjusted treatment based on mNGS results can reduce the 28-day and 90-day mortality of patients with severe pneumonia, and shorten the length of hospital and ICU stay. Therefore, mNGS advised to be applied to severe pneumonia patients as early as possible in addition to conventional methods to improve the prognosis and reduce the length of hospital stay.